'Certificated Operators' versus 'Handle-Turners': The British Film Industry's First Trade Union. Issue 1 (January 2018) - Burrows, Jon
Abstract : This article examines the history of the British film industry's first trade union: the National Association of Cinematograph Operators (NACO), an organisation for projectionists established in 1907. The deterioration in pay and working conditions experienced by projectionists following the advent of permanent cinemas is outlined, but, contrary to prevailing wisdom, it is pointed out that NACO was not actually formed in response to these developments. NACO pre-dated the growth of fixed-site film exhibition venues and the reasons behind its inception are explained in relation to the politics of the music hall industry. It is shown that the union's executive steadfastly promoted a conception of projection work that was rapidly becoming anachronistic in several respects, and concentrated their campaigning efforts upon trying to police entry into the profession, primarily via a proposed parliamentary bill to make an annual examination of projectionists' fitness to 'strike the arc' compulsory. It is argued that this was an inadequate and blinkered response to the increasing exploitation of projectionists as sweated labour, and also that NACO's repeated denunciation of inexperienced projectionists as 'handle-turners' may have emboldened employers in their determination to drive wages down. Consequently, although NACO belatedly decided to relax its membership requirements, new subscriptions were in decline by 1912 and the union remained inactive throughout the First World War until it was wound up and replaced in 1919.